Zero ischaemia laparoscopic nephron-sparing surgery by re-suturing - Lu, Jinshan; Zu, Qiang; Du, Qingshan; Xu, Yong; Zhang, Xu; Dong, Jun (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : To report a pre-suture technique in laparoscopic nephron-sparing surgery (LNSS), which could help reduce and even avoid ischaemia for the treatment of renal cell carcinoma. Material and methods: Between January and June 2013 we treated 14 patients presenting with renal tumours. The mean age was 46 years and average tumour size was 2.4 cm in diameter determined by computed tomography (CT). All the patients were treated with LNSS by pre-suturing the resection. Results: In 13 out of the 14 cases, no clamping was needed during the whole surgery processes, i.e. zero ischaemia was achieved. In the other case, the renal artery was clamped for only 150 seconds due to suture avulsion. The mean operating time was 75 minutes (range 50 to 110 minutes) and mean blood loss was 60 ml (range 30 to 200 ml). After removal of the drain 2–3 days after surgery, the average postoperative hospital stay time was four days. The surgery had only a minor effect on the renal function. No case of urinary leakage or postoperative bleeding occurred. Postoperative pathological reports showed that the tumours were resected completely with negative surgical margins for all cases. There were no signs of recurrence on follow-up CT performed 1–6 months after surgery. Conclusions : The pre-suture technique in LNSS reported here required zero or minimal ischaemia time and hence avoided renal ischaemia-reperfusion injury. This surgical technique could be a feasible surgical option for treatment of small, exophytic and peripheral renal tutors.